Effect of disinfectant agents on certain physical and mechanical properties of type IV dental stone - Hanan Abdul- Rahman Khalaf; Mithaq Radhi Mohammed (College of Dentistry/ University of Baghdad, 2014)
Background: Dental stone casts come into contact with impression materials and becomes susceptible to cross contamination from saliva and blood. This study was done to evaluate the physical and mechanical properties of dental stone type IV after treatments with various disinfecting agents and regimes (methods). Materials and Methods: Type IV dental stone and different types of disinfecting agents were used and divided into seven groups: G1: dental stone without disinfection (control group), G2: dental stone mixed with silver nitrate powder 0.5% , G3: dental stone mixed with silver nitrate powder 1%, G4: dental stone mixed with copper sulfate powder 0.5%, G5: dental stone mixed with copper sulfate powder 1% ,G6: dental stone immersed in propanol 70% and G7: dental stone immersed in ethanol 70%.Setting time, linear setting expansion, surface detail reproduction, compressive strength of type IV dental stone as well as compatibility with auto mixing addition silicone impression material were evaluated. The statistical analysis were conducted by ANOVA test followed by LSD test (p